A Study on Optical Camera Communication using Gaussian Window - Young Park, Chi; Young Shin, Soo (International Journal of Engineering and Technology, 2018)
Optical Camera Communication (OCC) is a Visible Light Communication (VLC) technique using a camera mounted on a digital device as a receiver. Nowadays, most digital devices are equipped with cameras using CMOS Image Sensors (CIS). In this paper, OCC is designed by using Rolling Shutter (RS), which is image output method of CIS. The transmitted data is captured using a camera application built in smartphone, and processed by MATLAB to restore the data. In this paper, we reduce the error rate by performing signal processing using Gaussian Window (GW) on the receiver side without using high-performance camera or directly controlling camera. In addition, we presented the avaliable range of transmission speed of OCC for indoor wireless communication and compared it with throughput in receiver side.
Keywords: Optical Camera Communication (OCC); Visible light Communication (VLC); Image Sensor Communication (ISC); Indoor communicatioin; Rolling Shutter (RS)